An evaluation for the use of alternative vehicle technologies and energy resources in logistic sector with a strategic approach - Mızrak, Filiz (Springer Science and Business Media Deutschland GmbH, 2022)
Increasing global energy consumption results in important problems. The decrease in traditional energy resources such as oil, coal, and natural gas reveals the necessity of using these resources more efficiently. In this scope, being one of the most key functions in the workflow of most business, logistics activities should be taken into consideration since these activities have a direct impact on issues such as environment, air pollution, and climate change. It is known that 60% of the oil and 25% of the energy used in the world is consumed by the transportation sector. This situation directly concerns environmental sustainability. In this respect, the purpose of the study is to review the most recent literature to evaluate the alternative vehicle technologies and fuels for logistic activities and propose the most practical, environmental friendly, and cheapest technology. As a result of the evaluation, it has been found out that electrical vehicles can be the most convenient ones in terms of sustainable logistics activities despite some drawbacks. Thus, some strategies have been put forward to increase the use of these vehicles in the near future.
Keywords: Alternative Energy Resources; Logistics; Strategy